CRISPR-barcoding in non small cell lung cancer: from intratumor genetic heterogeneity modeling to cancer therapy application - Zito Marino, Federica; Accardo, Marina; Franco, Renato (Journal of Thoracic Disease, 2017)
Cancers are composed of different populations of cells with distinct molecular and phenotypic characteristics that could have potential impact on cancer progression, tratment and risk of disease relapse (1). Genomic studies have demonstrated that human cancers comprise a molecular mosaic of cells, spatially and temporally different (2).